2020
DOI: 10.1177/2167479520922182
|View full text |Cite
|
Sign up to set email alerts
|

The Face of Mental Health: Kevin Love and Hegemonic Masculinity in the NBA

Abstract: While public discussion about mental illness has become increasingly common in the United States, previous research has found that having a mental illness diagnosis is assumed to be incompatible with elite athletic success. As explored in hegemonic masculinity scholarship, to be successful, professional male athletes attempt to physically dominate opponents. In 2018, National Basketball Association (NBA) star Kevin Love disclosed having a panic attack during a game as well as living with depression and anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…For instance, in coverage related to DeRozan’s admission, headlines included “Cavs’ Love mans up to mental health problems” and “DeRozan, Love help write a new playbook of manhood.” The fact that this research does not exist in isolation gives further support to an idea of a more inclusive masculinity. Parrott et al (2019) and Lavelle (2020) noted similar findings of the support NBA players received with their mental health concerns, while the “no pain, no gain” mentality of physical masculinity has been waning in recent years in sports media coverage (Cassilo & Sanderson, 2018; Sanderson et al, 2016). Meanwhile, leagues and organizations are devoting more resources to the health and welfare of athletes.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…For instance, in coverage related to DeRozan’s admission, headlines included “Cavs’ Love mans up to mental health problems” and “DeRozan, Love help write a new playbook of manhood.” The fact that this research does not exist in isolation gives further support to an idea of a more inclusive masculinity. Parrott et al (2019) and Lavelle (2020) noted similar findings of the support NBA players received with their mental health concerns, while the “no pain, no gain” mentality of physical masculinity has been waning in recent years in sports media coverage (Cassilo & Sanderson, 2018; Sanderson et al, 2016). Meanwhile, leagues and organizations are devoting more resources to the health and welfare of athletes.…”
Section: Discussionmentioning
confidence: 77%
“…In this way, DeRozan and Love were presented as mental health advocates. Lavelle (2020) examined Love’s experience further by performing a critical discourse analysis of the sports media coverage of his disclosure and mental health advocacy. Her analysis found that Love’s identity as a White athlete gave him the ability to come forward and was praised for doing so, yet he is still constrained by the NBA’s hegemonic masculinity.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Love, DeRozan, Keyon Dooling, Metta World Peace) are still in the minority (Pinto, 2019). According to Lavelle (2020), NBA players are hesitant to come forward about personal mental health concerns because they are often treated as an anomaly, while concerns about their performance capability fester. Indeed, Love did experience stigmatisation from his teammates after his panic attack.…”
Section: Social Biasesmentioning
confidence: 99%
“…It is also evident that representations of machismo and hard masculinity are nearing expiry with public discussions about male vulnerabilities and fragile masculinity entering mainstream consciousness. In the social media sphere, talks about mental health, male depression and anxiety have become increasingly common in addressing toxic masculinity (Lavelle, 2020). Importantly, the socially constructed images of a rough and tough masculinity through embodied physical muscularity and emotional stoicism in particular, are actively renegotiated and replaced with softer traits encompassing values such as nurturance, empathy and sensitivity (Lee & Lee, 2018).…”
Section: Countering Hegemonic Masculinitymentioning
confidence: 99%